A New Affinity Gel Synthesized for Phenylalanine Ammonia Lyase Isolated from Red Clover (Trifolium pratense L.) Leaf and an Investigation into Its Kinetic Properties - Toksoz, Yavuz Selim; Bilen, Cigdem; Karakus, Emine (MDPI, 2025)
Phenylalanine ammonia lyase (PAL) was first purified using affinity chromatography from the leaves of red-flowered clover, a highly antioxidant source. The characterization results of the PAL enzyme were determined, including the concentration of its activity buffer solution, pH, and temperature, which were 0.1 M, 7, and 25 degrees C, respectively. The Vmax and KM values of the enzyme were calculated to be 0.97 EU and 0.68 mM, respectively. L-phenylalanine was used as the substrate. All kinetic studies were performed spectrophotometrically with a wavelength of 283 nm. Sepharose-4B-L-tyrosine-4-aminocinnamic acid (S-4B-TACA) was also synthesized for the first time and used as an affinity gel. The activity of the PAL extract was measured as 267.9 (millienzyme unit) mU per mL. The yield % and purification fold in the purification step of affinity chromatography were determined to be 3.8% and 19.4, respectively. The experimental results indicate that the PAL enzyme was successfully purified using affinity chromatography. The purity of the enzyme was controlled via SDS-PAGE analysis, which indicated that PAL gave a clear, single band at the line of 45 kDa, while the PAL homogenate gave two bands at around 35 and 45 kDa. Enzyme stabilization was also investigated using PAL stored at 4 degrees C, which retained completely protected activity for the first 3 weeks. The synthesis of the S-4B-TACA affinity gel, the purification of PAL from red clover leaves using affinity chromatography, and its characterization and statistical analysis have not been previously investigated or reported in the literature.
Keywords: Trifolium pratense L.; phenylalanine ammonia lyase; affinity chromatography; purification; characterization; SALICYLIC-ACID; ENZYME; LIGNIFICATION; BIOSYNTHESIS; METABOLISM; STRESS; ASSAY; PAL; Chemistry